Social media utilization in Covid-19 epoch: Virtual da’wah-ramadan lectures in Northern Nigeria - Sule, Muhammad Maga (Jurnal Ilmu Dakwah, 2020)
Social media have become part of the individual and public lifestyles of Muslims globally. The paper examined the utilization of social media platform such as Facebook and YouTube as an available option to conduct Virtual Da’wah Ramadan lectures on the commentary of the Glorious Qur’an and Ta’aleem in Northern Nigeria and this was done with the sampled of scholars from the three zones in Northern Nigeria, i.e. North-West, North-Central and North-East. The paper adopts the use of secondary data as method of data collection where In-depth survey of the various pages/channels on social media and participant observation to obtain data. The researchers purposively sampled nine scholars for the study and survey was carried out on their various social media pages/channels to ascertain their level of utilization of the technology during the COVID-19 period to teach their followers with the restriction of movement and gathering in places of worship in Nigeria.  Some of the findings of the study revealed that the sampled Muslims scholars finds it convenient to present live programme of their teachings virtually and post video and audio of their Virtual Da’wah Ramadan lectures on the commentary of the Glorious Qur’an and Ta’aleem social media. The research paper concludes Muslim scholars to continue with the utilization of the social media platforms even after the Ramadan and Post-COVID-19 pandemic in carrying out their day to day virtual teachings so that other audience who are not close to their Masjid will benefit from their lectures on the various teachings of Islam.